Gingerol: Anti-inflammatory Compound in Ginger (Zingiber officinale) as Potential Drug Ingredient for Rheumatoid Arthritis - Azmi, Naurah Arika; Arsy, Lazuardi; Faqih, Fauzan; Lukman, Dian Azizah; Fariztia, Alifia Intan; Haq, Andi Muhammad Al Fatih; Mujahid, Sabila Izzatina Azmy (Jurnal Biologi Tropis, 2024)
Rheumatoid arthritis (RA) is a chronic autoimmune disease that affects the joints, with a global prevalence of approximately 0.5-1% of the adult population. Conventional RA treatments often have side effects, prompting the exploration of alternative options. This study aims to explore and review the potential of gingerol, an anti-inflammatory compound found in ginger (Zingiber officinale), as a treatment for RA. The method used was a literature review of 39 relevant articles. The results indicate that gingerol exhibits anti-inflammatory activity by inhibiting pro-inflammatory cytokines and modulating inflammatory pathways. In conclusion, gingerol from ginger shows significant potential as an alternative treatment for RA, although further research is needed to overcome challenges in the extraction process and product development.